A Socio-Onomastics Study of a Church Naming Content on legit.ng - James Oladunjoye Faleye; Eunice Olatokunbo Fajobi; Ibrahim Esan Olaosun (CV. Rustam, 2026)
This paper is a Socio-onomastic analysis of a church-naming content, posted on www. Legit.ng , an online forum where young Africans share contents of all kinds. The content consists of the signboards and programme flyers of some hypothetical churches in Nigeria. The naming component of these signposts and flyers serves as the data for this article, which is aimed at expounding the underlying discourse significance of the socially-constituted genre of religious discourse. Using the principles of Socio-onomastics and insights from Eco’s Textual Cooperation Theory and the notion of diegesis in Narratology, analysis of the data shows that the names in the signposts and flyers, though congruently fictional in form, are true narratives of the church naming practices amongst ‘commercial church owners’ in Nigeria. The paper concludes that although the church names fictionalized not directly reference specific real church names in Nigeria, they mirror certain societal values and ideologies of breakthrough in the country rather than merely serving as entertainment construction.